2015
DOI: 10.1155/2015/707254
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokine of IL-10 and IL-12 in Chronic Liver Disease: The Immune and Inflammatory Response

Abstract: The current study was designed to investigate the potential association of serum interleukin-10 and interleukin-12 with HCV infection in chronic liver disease and to evaluate their possible role as new biomarkers in HCC development. Material and Methods. Forty-one patients suffering from chronic liver disease (33 patients harbor HCV infection and 8 are HCV-negative patients) were enrolled in the present study and histopathologically diagnosed into 15 patients with HCC, 16 patients with LC, and 10 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 31 publications
5
31
1
Order By: Relevance
“…Similar to previous work, we show elevated IL‐10, an anti‐inflammatory cytokine in our HBV‐infected and HDV‐infected cohorts (Fig. ) . Rise in IL‐10 along with corresponding decline in type 1/regulatory type, type 2/regulatory type, and type 3/type 2 ratios indicates heightened regulatory immunity with disease progression (Table ) and reinforces a possible role of IL‐10 in infection chronicity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to previous work, we show elevated IL‐10, an anti‐inflammatory cytokine in our HBV‐infected and HDV‐infected cohorts (Fig. ) . Rise in IL‐10 along with corresponding decline in type 1/regulatory type, type 2/regulatory type, and type 3/type 2 ratios indicates heightened regulatory immunity with disease progression (Table ) and reinforces a possible role of IL‐10 in infection chronicity.…”
Section: Discussionsupporting
confidence: 90%
“…3). 6,16,42,43 Rise in IL-10 along with corresponding decline in type 1/regulatory type, type 2/regulatory type, and type 3/type 2 ratios indicates heightened regulatory immunity with disease progression (Table 3) and reinforces a possible role of IL-10 in infection chronicity.…”
Section: Innate Immunity In Hepatitis B and Dmentioning
confidence: 84%
“…The results of the present work showed that both HCV-AI and HCV-NAI patients had significantly higher levels of IL-10 compared to healthy controls which agrees with both Piazzolla et al [50] who showed that serum IL-10 levels were higher among chronic HCV patients compared to controls, and El-Emshaty et al [22] reported the same on Egyptian subjects. Mikadze and Vashakidze [54] reported a significant rise of IL-10 concentration in cases of severe hepatic lesions.…”
Section: Discussionsupporting
confidence: 91%
“…A study on Egyptian patients' demonstrated higher serum IL10 and TNF-α levels compared to non-infected control [15,16,22]. B cell activating factor (BAFF) is essential in B lymphocytes development, maturation and activation [23].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin (IL)‐10, an immunomodulatory cytokine mainly secreted by regulatory T cells, monocytes and macrophages, has important roles in inducing immune tolerance by inhibiting antigen‐specific T‐cell proliferation, downregulating costimulatory molecule and MHC II expression on antigen‐presenting cells, inhibiting DC maturation, and inhibiting the production of proinflammation factors, such as tumour necrosis factor (TNF)‐α, interferon‐γ, IL‐6 and IL‐12 . Some studies reported that IL‐10‐producing DCs mediate tolerogenic effects by inhibiting T‐cell activation and enhancing the differentiation of regulatory T cells, which suggests IL‐10 is a potential therapeutic factor for inducing immunological tolerance after LT. Fas ligand (FasL) expressed on antigen‐presenting cells is a type II transmembrane protein belonging to the tumor necrosis factor superfamily, which combines with Fas expressed on T cells to initiate the apoptosis of specific activated T cells, resulting in the downmodulation of immune responses and maintenance of T‐cell tolerance .…”
Section: Introductionmentioning
confidence: 99%